Kegagalan Sistem Keselamatan Transportasi Laut di Indonesia - Habibi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
Sea transportation is the artery for an island nation. Indonesia, which has a large number of islands, needs adequate sea transportation facilities. Ironically, as a maritime country the Indonesian sea transportation system is in shambles. This is proven by the large number of accidents at sea. Marine ship crashes caused hundreds of lives of Indonesian people to float. The causes of accidents vary, ranging from fires, overloading to the age of the manipulated vessels. This condition is exacerbated by the weak level of supervision from policy makers. The government's mistake in its current national development policy is to prioritize land base oriented. So that strategies related to sea affairs do not get priority. As a result of the wrong strategy, the policies and implementation in the field of sea transportation are chaotic. As a consequence, sea transportation which should be the mainstay of the community actually becomes a frightening transport. The level of ship accidents is a consequence of lost control. Without warning, the shipping operator / operator determines a cautious attitude towards accidents at sea. Ship accidents at sea not only give consequences to casualties but also costs that must be borne to cover the trend of the ship's accident.